Apparent Diffusion Coefficient for Distinguishing Between Malignant and Benign Lesions in the Head and Neck Region: A Systematic Review and Meta-Analysis - Surov, Alexey; Meyer, Hans Jonas; Wienke, Andreas (Frontiers in Oncology, 2020)
Background: The purpose of the present meta-analysis was to provide evident data about use of ADC values for distinguishing malignant and benign lesions in the head and neck region. Material and Methods: MEDLINE and SCOPUS databases were screened for associations between ADC and malignancy/benignancy of head and neck lesions up to December 2018. Overall, 22 studies met the inclusion criteria. The following data were extracted: authors, year of publication, study design, number of patients/lesions, lesion type, mean value and standard deviation of ADC. The primary endpoint of the systematic review was the analysis of the association between lesion nature and ADC values. The methodological quality of the involved studies was checked according to the UADAS instrument. The meta-analysis was undertaken by using RevMan 5.3 software. DerSimonian and Laird random-effects models with inverse-variance weights were used without further correction to account for the heterogeneity between the studies. Mean ADC values including 95% confidence intervals were calculated separately for benign and malign lesions. Results: The acquired 22 studies comprised 1227 lesions. Different malignant lesions were diagnosed in 818 cases (66.7%) and benign lesions in 409 cases (33.3%). The mean ADC value of the malignant lesions was 1.04 x 10-3 mm2/s and the mean value of the benign lesions was 1.46 x 10-3 mm2/s. Lymphomas and sarcomas showed lowest calculated mean ADC values, 0.7 and 0.79 x 10-3 mm2/s, respectively. Adenoid cystic carcinomas had highest ADC values (1.5 x 10-3 mm2/s). None of the analyzed malignant tumors had mean ADC values above 1.75×10-3 mm2/s. Conclusion: ADC values play a limited role in distinguishing between malignant and benign lesions in the head and neck region. It may be only suggested that lesions with mean ADC values above 1.75×10-3 mm2/s are probably benign. Further large studies are needed for analysis the role of DWI/ADC in discrimination benign and malignant lesions in the head and neck region.